If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(8 + -6h) = h (8 * 0.5 + -6h * 0.5) = h (4 + -3h) = h Solving 4 + -3h = h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. 4 + -3h + -1h = h + -1h Combine like terms: -3h + -1h = -4h 4 + -4h = h + -1h Combine like terms: h + -1h = 0 4 + -4h = 0 Add '-4' to each side of the equation. 4 + -4 + -4h = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -4h = 0 + -4 -4h = 0 + -4 Combine like terms: 0 + -4 = -4 -4h = -4 Divide each side by '-4'. h = 1 Simplifying h = 1
| -20m=-460 | | -4c+9=42 | | 60=4(6)(2)+2(2)h | | w/3=75 | | 4(u-15)=4 | | (x^18)^1/18 | | n-3-4n=15 | | 22=7m+1 | | 3/5=p | | 208=8+8+8+8+6+6m | | 7-2x=85+4x | | 2+5a=17 | | 9z-3/3z-1=5 | | 3/5(x+4)=33 | | 5*x-7=-6*x-29 | | 10=b(5) | | 3p=5 | | b-1=-9 | | 180=115+x+x | | X-3/5x | | 2x+8+6x-4=84 | | 7=3y-17 | | 6x-(4x-32)=0 | | 125m-100m+43,650=45,675-300m | | (16x-3)(4)=0x | | 4(6p-3)=-39-3p | | -.4*p+2=.2*p+11 | | (16x-3)(4)=0 | | 10x-6=7x | | y+(-10)=36 | | 8y+1=2y-26 | | .5f+10=48 |